Giant enhancement of second harmonic generation from monolayer 2D materials placed on photonic moiré superlattice - Ning, Tingyin; Zhao, Lina; Huo, Yanyan; Cai, Yangjian; Ren, Yingying (Nanophotonics (Berlin, Germany), 2023)
We numerically investigate second harmonic generation (SHG) from a monolayer of 2D-material placed on photonic moiré superlattice fabricated by dielectric materials. The greatly enhanced local field at the resonance modes of moiré superlattice can dramatically boost the SHG response in 2D materials. Considering a typical 2D-material MoS monolayer placed on a photonic moiré superlattice of a twist angle 9.43°, the maximum SHG conversion efficiency reaches up to 10 at a relatively low intensity of fundamental light 1 kW/cm , which is around 14 orders of magnitude larger than that from the monolayer placed on a flat dielectric slab without moiré superlattices. The SHG conversion efficiency from the monolayer can be further enhanced with the decrease of the twist angles of moiré superlattice due to the even more confinement of local field. The flat bands in the moiré superlattices formed by the small twist angles can particularly ensure the efficiency even under wide-angle illuminations. The results indicate that photonic moiré superlattice which can tightly confine light is a promising platform for efficient nonlinear optics.